2016
DOI: 10.2139/ssrn.2741001
|View full text |Cite
|
Sign up to set email alerts
|

Access to Short-Term Credit and Consumption Smoothing within the Paycycle

Abstract: I study the effect of access to payday loans on the timing, level and composition of consumption. Using a newly obtained military administrative dataset of sales at on-base grocery and department stores, I examine how consumption behavior changes after the passage of a federal law that effectively bans military personnel from accessing payday loans in some states but not others. The military setting is ideal for this analysis because military personnel are assigned to locations across the United States with va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…To that end, Gjertson (2014) reports that households that save for emergencies are less likely to be food insecure, and other recent work suggests liquidity constraints are particularly salient with regards to food insecurity among the poor and those just above food assistance eligibility thresholds (Chang, Chatterjee, and Kim 2014). Consistent with the importance of liquidity constraints, some evidence suggests access to short-term credit in the form of payday loans may smooth food consumption and reduce the risk of food insecurity (Fitzpatrick 2013;Fitzpatrick and Coleman-Jensen 2014;Karlan and Zinman 2010;Zaki 2016). This research is decidedly mixed, however, with other studies finding detrimental impacts (e.g., Chang and Perry 2015).…”
Section: Background: Food Insecurity Income and Financial Behaviorsmentioning
confidence: 97%
“…To that end, Gjertson (2014) reports that households that save for emergencies are less likely to be food insecure, and other recent work suggests liquidity constraints are particularly salient with regards to food insecurity among the poor and those just above food assistance eligibility thresholds (Chang, Chatterjee, and Kim 2014). Consistent with the importance of liquidity constraints, some evidence suggests access to short-term credit in the form of payday loans may smooth food consumption and reduce the risk of food insecurity (Fitzpatrick 2013;Fitzpatrick and Coleman-Jensen 2014;Karlan and Zinman 2010;Zaki 2016). This research is decidedly mixed, however, with other studies finding detrimental impacts (e.g., Chang and Perry 2015).…”
Section: Background: Food Insecurity Income and Financial Behaviorsmentioning
confidence: 97%
“…Baugh (2015) shows that following online payday loan restrictions, households reduced bounced checks and increased consumption by 3%. On the positive side of the empirical findings, authors have found that access to payday loans mitigates foreclosures following natural disasters (Morse ), helps households smooth spending between paychecks (Zaki ), and that banning payday lending results in more bounced checks and complaints against debt collectors (Morgan, Strain, and Seblani ). Zinman () finds that capping payday loan interest rates leads to households reporting a decline in overall financial conditions.…”
Section: Payday Loan Laws By State During Sample Periodmentioning
confidence: 99%
“…More recently, Michelmore and Jones () show that high cost borrowing often happens when poor households anticipate tax rebates that are paid yearly in a lump‐sum fashion. Zaki () also finds that, for consumers who do not have access to credit, food expenditures spike on payday and are significantly lower at the end of the pay period. She documents that food consumption is not smooth, even for a pay period that is biweekly.…”
Section: Introductionmentioning
confidence: 99%